Textual amulets from antiquity to early modern times: the shape of words - Theis, Christoffer; Vitellozzi, Paolo (Bloomsbury Academic, 2023)
Intro -- Half Title -- Series Page -- Title Page -- Copyright Page -- Contents -- Figures -- Preface -- Contributors -- Chapter 1: Textual Amulets from a Transcultural Perspective -- Chapter 2: Writing on Magical Gems: Reflections on Inscribed Gemstone Amulets of the Imperial Period -- Chapter 3: Of Comprehensible and Incomprehensible Inscriptions: Remarks on Some Gems with Multi-headed Gods -- Chapter 4: Agency and Efficacy in Syriac Amulets across the Ages -- Chapter 5: Demons in Runic and Latin Amulets from Medieval Scandinavia -- Chapter 6: Magic Letters: Unintelligible Prophylactic Formulas -- Chapter 7: The Materiality of Talismans from Early Modern Spain: Morisco (and Old-Christian) Cases -- Chapter 8: Talismans and Engravers of Talismans in the Seventeenth-Century Ottoman Society According to the Journal of Evliyā Çelebi -- Chapter 9: Small Letters against Great Misfortunes: A Glance at Safavid Amulet Culture -- Chapter 10: Final Remarks: Toward a Transcultural View of Magical Writing -- Notes -- Bibliography -- Index of Sources -- Index of Names -- Index of Places -- General Index.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Geschichte 500 v. Chr.-2000; Schrift; Amulett